Enhancing performance characteristics of equipment of sea and river transport by using epoxy composites - Buketov, Andriy; Maruschak, Pavlo; Sapronov, Oleksandr; Zinchenko, Dmytro; Yatsyuk, Vitaliy; Panin, Sergey (Transport, 2016)
Coatings based on epoxy diane oligomer ED-20 are being developed as environmentally benign, foulingresistant marine coatings. Silver oxide and carbonate (mixture) was used as filler, the dispersion of which is 0.5 µm. It is proved that for the formation of composites with the improved physical and mechanical properties it is necessary to add Mechanical Mixture of Silver Carbonate and Oxide (MMSCO) in the amount of q = 0.050…0.250 pts. wt. into the epoxy diane oligomer ED-20 (100 pts. wt.). The obtained values of impact toughness of composites during the introduction of MMSCO into the binder increased by 2.5 times compared to the epoxy matrix. Moreover, the maximum capacity to resist impact loads, including fracture toughness, was demonstrated by the Composite Material (CM) with the filler content q = 0.050 pts. wt. Impact toughness of this CM is а = 18.53 kJ/m2. The developed materials and protective coatings based on them were used on the dry cargo ship Oles Honchar.